(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The increasing demand for engineers and technical specialists with proficient English communication skills presents a significant challenge for higher education institutions. Traditional language teaching methods often fail to bridge the gap between theoretical knowledge and practical application in a professional context. This paper proposes a novel pedagogical framework, “Communicative Project-Based Learning” (CPBL), designed specifically to enhance technical English proficiency in higher education, with a particular focus on engineering and technology disciplines. Rooted in a comprehensive model of communicative competence, the CPBL framework synergizes established pedagogical strategies with modern, project-centric learning. It positions practical, real-world projects as the core learning experience, requiring students to collaboratively engage in technical tasks where the use of English for communication, problem-solving, and presentation is both necessary and natural.